ANGELA CARTER’S THE BLOODY CHAMBER: A FEMINIST STYLISTIC APPROACH - Arıkan, Seda (Fırat University, 2016)
Stylistics, the study of a writer’s style, has incorporated various approaches, especially in the last few decades. Therefore, feminist stylistics based on the theories of feminist criticism appears as a significant approach defining “woman” and her place not only in society, but also in language. By examining male domination in society and literary works, feminist stylistics tries to present a counter-image of women both in language and social construction. The tendency of current feminist stylistics mostly focuses on the idea that there is a significant “women’s writing and style” that differs from men’s. These linguistic and thematic differences that are called “genderlect” or “gendered sentence” in women’s writing are the main interest of feminist stylistics. This study will depict the “genderlect” and “gendered” style in Angela Carter’s The Bloody Chamber. Carter’s The Bloody Chamber, a collection of re-written traditional fairy tales, “extracts the latent content from the traditional stories” in Carter’s words. Ten stories in the collection handle the topics of marriage, sexuality, gender roles, and female liberty with a subverting point of view. In this article, three stories narrated by female first-person narrators in this collection will be analyzed in terms of lexico-semantic items in the narration, and Carter’s style as an example of écriture féminine will be examined with regard to feminist stylistics.

Bir yazarın yazın üslubunu inceleyen deyişbilim özellikle son yirmi otuz yıldır çeşitli yaklaşımları bir araya getirmiştir. Bu nedenle, feminist eleştiri üzerine temellenen feminist deyişbilim, kadını ve kadının konumunu sadece toplumda değil dilde de tanımlayan önemli bir yaklaşım olarak ortaya çıkar. Feminist deyişbilim, toplumdaki ve edebi eserlerdeki erkek egemenliğini inceleyerek, hem dil hem de toplum yapılanmasında kadın için bir karşı-imge sunmaya çalışır. Mevcut feminist deyişbilim yaklaşımı, erksel olandan ayrılan önemli bir “kadın yazını ve deyişi” olduğu fikrine yoğunlaşır. Kadın yazınındaki “toplumsal cinsiyet değişkesi” ya da “toplumsal cinsiyetli deyiş” olarak adlandırılan bu dilbilimsel ve tematik farklar feminist deyişbilimin en temel ilgi alanıdır. Bu çalışma, Angela Carter’ın The Bloody Chamber adlı anlatısında “toplumsal cinsiyet değişkesi” ya da “toplumsal cinsiyetli deyiş”i dile getirecektir. Geleneksel masalların yeniden yazıldığı bir derlem olan Carter’ın The Bloody Chamber anlatısı, Carter’ın kendi deyişiyle “geleneksel öykülerdeki gizil içeriği ortaya çıkarır”. Derlemdeki on öykü evlilik, cinsellik, toplumsal cinsiyet ve kadın özgürlüğü konularını düzeni bozan bir bakış açısı ile ele almaktadır. Bu makalede, derlemden seçilmiş, birinci şahıs kadın anlatıcılar tarafından aktarılan üç öykü anlatıdaki sözcük-anlambilimsel öğeler açısından irdelenecek, écriture féminine örneği olarak Carter’ın üslubu feminist deyişbilim bakımından incelenecektir.
Angela Carter’ın The Bloody Chamber Adlı Anlatısı: Feminist Deyişbilimsel Bir Yaklaşım